Empowering Women Association of Religious Affairs Department in South Sumatera through Communication and Video Editing Skills (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The South Sumatera Women's Association, under the Religious Affairs Department, was the beneficiary of the community service initiative.  Their frequent professional development programs, their inability to complement video editing operations with technical abilities, and their low understanding of public speaking for communication served as the impetus for this empowerment program. Forty-five association members took part in this initiative.  According to their interviews, the majority of them lacked video editing abilities, with only a small percentage having rudimentary understanding but being unable to use video editing software efficiently. They also experienced anxiety when speaking in front of large crowds. By offering training targeted at improving their interest and proficiency in video editing and communication, this community service project sought to close this gap. The use of CapCut was the main emphasis of the instruction. Among the techniques used were workshops and seminars. According to the findings, 90% of the participants felt comfortable using their communication skills and were able to effectively apply the video editing techniques that were covered in the training sessions. In our technologically advanced society, it is anticipated that this training will greatly empower women.